Preventive competence of an educational psychologist: the connection with diagnostics and art methods (Journal of Educational Sciences, 2025)
Maintaining the mental health of students is an important task of the education system and the work of a psychologist at school and university. In 2022, the UNESCO International Organization published the "Strategy for Education for Health and Well-being", which implements the UN Sustainable Development Goals, including the preservation of the health and well-being of students. Psychoprophylaxis, as a type of activity of an educational psychologist or educational psychologist, is aimed at preserving, strengthening and developing mental health. Therefore, it is important in the professional training of future psychological educators to focus on the development of preventive competence, which is associated with the diagnosis and training of coping strategies, art technologies for self-regulation of emotions, and psychophysiology of schoolchildren and students. In the theoretical part of the article, the preventive competence of the future teacher-psychologist, educational psychologist is designed, the directions of primary, secondary, and tertiary prevention by art methods are analyzed. Creativity and art techniques allow you to regulate your emotions and mood. Therefore, the practical part of the study examines the relationship between the tendency to depression, self-esteem and creativity among university psychology students.  The study involved 50 students who were assessed for depression, self-esteem, and creativity. The results indicate a negative correlation between indicators of depression and creativity, as well as between depression and self-esteem, confirming the detrimental effects of depression on emotional and cognitive well-being. It has been found that improving self-esteem can help reduce the negative impact of depression on students' creative abilities.Key words: preventive competence of a psychologist, educational psychologist, propensity to depression, mental health, self-esteem, creativity.